Klein-Gordon oscillator interacting with screened Kratzer potential in a cosmic string space-time with space-like dislocation and AB field - Alrebdi, H. I.; Ikot, A. N.; Okorie, U. S.; Rampho, G. J.; Horchani, R. (Frontiers in Physics, 2025)
In this paper, we examine the relativistic quantum behaviour of spinless particles interacting through the Klein-Gordon (KG) oscillator and screened Kratzer potentials and influenced by external magnetic field, using the extended Nikiforov-Uvarov method. A detailed analysis of how quantum numbers and cosmic string parameters affect the energy spectra of the KG oscillator are provided. The results obtained reveal that energy spectra are influenced by the quantum numbers and the cosmic string parameters thereby causing a shift, depending on the quantum magnetic flux, dislocation parameter, and other potential parameters considered. Our results agree with results in literature and the study proves to be very useful in the understanding of the behavior of particles in a cosmic space-time with space-like dislocation.